See inside science - Frith, Alex.; King, Colin, 1943- (London : Usborne ; Tulsa, Okla. : EDC, 2006)
Contains lift-the-flap facts about developments in the history of science, covering the origins of the universe, outer space, plant and animal life, the microscopic world, atoms and energy, molecules, DNA, and other topics.
Cover title.
On lift-the-flap board pages.
3.5
K-3.
K-3
Keywords: Science -- Juvenile literature; Toy and movable books -- Specimens; Science; Toy and movable books; Science; Toy and movable books